Pengaruh Pemberian Ekstrak Propolis Terhadap Kadar Kolesterol Darah Tikus Wistar Jantan Setelah Dipapar Sidestream Cigarette Smoke (Effect of Propolis Extract on Blood Cholesterol Level in Male Wistar Rats After Being Exposed to Sidestream Cigarette Smoke - Chusna Sekar Wardani; Roedy Budirahardjo; Budi Yuwono (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Smoking is one of environment factors which caused a bad effect for health. TheSidestream Cigarette Smoke (SCS) contained in smoke produce free radicals highly andincrease total cholesterol levels. Elevated levels of total cholesterol can be treated withmedicine of statins, but its use in the long term cause side effects. Therefore, at thistime medicine has been developed from natural a substance which is expected haveless side effects, one of which is propolis. This research aims to determine whether thereis a decrease in total cholesterol levels in male Wistar rats (Rattus norvegicus) whichwas given extracts of propolis and exposed SCS. The research is experimentallaboratory with post test control group design. This research uses 12 rats which consistof 2 groups (1 control and 2 groups of treatment). The first treatment group is exposedby SCS. The second one is exposed by SCS and given the extract of propolis 2 times aday for 8 days. The total blood cholesterol level is measured by usingspectrophotometer with enzymatic colorimetric methods. The results of data analysisusing One Way Anova test shows there is a significant difference in total bloodcholesterol level means of male Wistar rats (p <0.05). While the Tukey HSD test showsthere is a significant difference in total cholesterol level means between groups, exceptbetween the control group and the second treatment group. Conclusion of thisresearch is that the propolis extract can lower total cholesterol levels of male Wistar ratswhich given exposure of Sidestream Cigarette Smoke.Keywords: blood cholesterol levels, propolis extract, sidestream cigarette smoke